Effects of athlete-dependent traits on joint and system countermovement-jump power - Williams, K. J.; Chapman, D. W.; Phillips, E. J.; Ball, N. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To establish the influence of athlete-dependent characteristics on the generation and timing of system and individual joint powers during a countermovement jump (CMJ). Methods: Male national representative athletes from volleyball (n = 7), basketball (n = 6), and rugby (n = 7) performed a set of 3 CMJs at relative barbell loads of 0%, 10%, 20%, 30%, and 40% of absolute back-squat strength. Ground-reaction forces and joint kinematics were captured using a 16-camera motion-capture system integrated with 2 in-ground force plates. Limb lengths and cross-sectional areas were defined using 3-dimensional photonic scans. A repeated-measures analysis of variance determined the interaction between system and joint load-power profiles, whereas a multiregression analysis defined the explained variance of athlete-dependent characteristics on the load that maximized system power. Results: System and isolated hip, knee, and ankle peak powers were maximized across a spectrum of loads between and within sports; power values were not significantly different across loads. A positive shift in the timing of hip and ankle peak powers corresponded to a significant (P < .05) positive shift in the timing of system peak power to occur closer to toe-off. An optimal 3-input combination of athlete-dependent characteristics accounted for 68% (P < .001) of the explained variance in the load that maximized system peak power. Conclusion: The load maximizing system power is athlete-dependent, with a mixture of training and heredity-related characteristics influencing CMJ load-power profiles. The authors recommend that a combination of relative loads be individually prescribed to maximize the generation and translation of system CMJ power.